2014
DOI: 10.1007/s40618-014-0189-z
|View full text |Cite
|
Sign up to set email alerts
|

Lean mass in obese adult subjects correlates with higher levels of vitamin D, insulin sensitivity and lower inflammation

Abstract: Our results show for the first time that in obese patients, higher amounts of lean mass are directly linked to a lower inflammatory profile and to better insulin sensitivity, but also to the presence of higher level of vitamin D and IGF-1. Moreover, these data suggest that higher levels of lean mass in obese people correlate with a better metabolic profile and, thus, strongly suggest the need to develop programs to facilitate an increase in physical activity in obese people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
25
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 25 publications
8
25
1
1
Order By: Relevance
“…The lean body mass values found in the Vitamin D Deficiency group are different from those reported in other studies, which showed a positive correlation between vitamin D and lean mass [41,42]. The high percentage of lean mass in the Vitamin D Deficiency group may be due to factors other than engagement in physical activities.…”
Section: Discussioncontrasting
confidence: 85%
“…The lean body mass values found in the Vitamin D Deficiency group are different from those reported in other studies, which showed a positive correlation between vitamin D and lean mass [41,42]. The high percentage of lean mass in the Vitamin D Deficiency group may be due to factors other than engagement in physical activities.…”
Section: Discussioncontrasting
confidence: 85%
“…These findings are also pertinent from the clinical perspective. Although weight loss studies have shown improvement in lung function in children and adults and higher lean mass is associated with higher vitamin D levels in adults, weight loss among children is modest and difficult to sustain, particularly among minorities . Since vitamin D deficiency is more common among obese children, is influenced by dietary habits, and is responsive to therapy, the association of vitamin D with lung volume deficits linked to obesity offers a therapeutic option for childhood obesity‐related asthma which is known to be less responsive to conventional asthma management .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the low adipose tissue content observed in DIO-R rats was accompanied by higher lean mass levels than those in DIO-S rats. Recent studies show that higher levels of lean (muscle) mass in obese individuals correlate with a better metabolic profile 45 . Skeletal muscle is an organ that produces molecules known as myokines 46 which have been proposed to protect from illnesses associated with physical inactivity 46,47 , and the inhibitory effect of exercise on mammary cancer cell proliferation may be partly mediated by some of these molecules 46 .…”
Section: Discussionmentioning
confidence: 99%